2005
DOI: 10.1152/ajplung.00109.2005
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic identification of novel early stress response genes in rodent models of lung injury

Abstract: Acute lung injury is a complex illness with a high mortality rate (>30%) and often requires the use of mechanical ventilatory support for respiratory failure. Mechanical ventilation can lead to clinical deterioration due to augmented lung injury in certain patients, suggesting the potential existence of genetic susceptibility to mechanical stretch (6, 48), the nature of which remains unclear. To identify genes affected by ventilator-induced lung injury (VILI), we utilized a bioinformatic-intense candidate gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
93
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(106 citation statements)
references
References 55 publications
12
93
0
1
Order By: Relevance
“…Quantitative real-time RT-PCR validation of selected candidate genes was conducted as previously described (23,24). Briefly, transcript levels of selected candidate genes in control and kidney IRI-treated lung tissues were measured (n ϭ 3/condition) in 96-well microtiter plates with an ABI Prism 7700 Sequence Detector Systems (PerkinElmer/Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative real-time RT-PCR validation of selected candidate genes was conducted as previously described (23,24). Briefly, transcript levels of selected candidate genes in control and kidney IRI-treated lung tissues were measured (n ϭ 3/condition) in 96-well microtiter plates with an ABI Prism 7700 Sequence Detector Systems (PerkinElmer/Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…Experimental parameters were 48°C for 30 min followed by 40 cycles of 95°C for 15 s and 60°C for 1 min. Relative gene expression was calculated using the 2 Ϫ⌬⌬Ct method, which generates fold-change values for mRNA transcript levels expressed in IRItreated lung samples relative to sham-operated samples as described previously (24).…”
Section: Methodsmentioning
confidence: 99%
“…were measured (n=3 per condition) as previously described [8]. Briefly, the 96-well microtiter plate setting of an ABI Prism 7700 Sequence Detector Systems (Perkin-Elmer/Applied Biosystems) was employed.…”
Section: Real-time Rt-pcrmentioning
confidence: 99%
“…Our lab and the others have demonstrated that expression analysis of underpowered array experiments complemented with compatible expression information from similar experimental settings produced biologically feasible results [6][7][8]. In current studies, we further utilized complementary information obtained from multiple probe-sets that target the same exon or UTR .…”
Section: Introductionmentioning
confidence: 99%
“…Вероятно, расшифровка данных механизмов позволит определить процесс инициации ОПЛ и системных эффектов данного синдрома. Новые технологии должны определить роль каждого регуляторного белка в изолирован ных клетках или в ткани организма, развитие посттрансляционных изменений и межмолеку лярные взаимоотношения белков, определяющих реализацию фенотипа клетки [59,60].…”
unclassified